The use of distraction as a pain management technique among nurses in a North-central city in Nigeria - Bukola Mary Ibitoye; Temitope Mary Oyewale; Kayode Simeon Olubiyi; Olayinka Abolore Onasoga (Elsevier, 2019)
Purpose: Distraction is an effective and readily-available pain management intervention which can be highly valuable in low-resource health facilities. It is an integral part of the pain management course in the nursing curriculum of many Nigerian universities. Hence, this study seeks to determine the gap between theory and clinical practice. The aim of this study is to assess the beliefs of nurses on distraction as a pain management intervention, and their use of distraction during clinical practice. Design: A descriptive survey was conducted. Methods: 170 questionnaires were distributed to nurses in a tertiary hospital in Nigeria. There was a response rate of 96%. Data were analyzed using both descriptive (such as frequency and percentages) and inferential statistics (such as chi-square). Results: Majority of the study participants were familiar with distraction and its use in pain management (98.8%). The majority of the participants (97.5%) indicated they use distraction as a pain management technique, and they (61.3%) believed that distraction can be effective, without administering any pharmacological agent. The nurses (84%) mostly used distraction to manage post-operative pain. Conclusion: From the nurses' perspective, it appears distraction is well-utilized in clinical practice. However, there is a need to educate nurses on the use of various distractors and other non-pharmacological interventions in order to improve pain management. Clinical implication: The use of distraction among Nigerian nurses is encouraging, but they should be cautious about using distraction alone for pain management. Nurses should endeavor to use distraction with a pharmacological agent, as appropriate.